First insight about the ability of specific glycerophospholipids to discriminate non-small cell lung cancer subtypes - Sieminska, Julia; Miniewska, Katarzyna; Mroz, Robert; Sierko, Ewa; Naumnik, Wojciech; Kisluk, Joanna; Michalska-Falkowska, Anna; Reszec, Joanna; Kozlowski, Miroslaw; Nowicki, Lukasz; Moniuszko, Marcin; Kretowski, Adam; et al. (Frontiers in Molecular Biosciences, 2024)
Introduction: Discrimination between adenocarcinoma (ADC) and squamous cell carcinoma (SCC) subtypes in non-small cell lung cancer (NSCLC) patients is a significant challenge in oncology. Lipidomics analysis provides a promising approach for this differentiation.In an accompanying paper, we explored oxPCs levels in a cohort of 200 NSCLC patients. In this research, we utilized liquid chromatography coupled with mass spectrometry (LC-MS) to analyze the lipidomics profile of matching tissue and plasma samples from 25 NSCLC patients, comprising 11 ADC and 14 SCC cases. This study builds upon our previous findings, which highlighted the elevation of oxidised phosphatidylcholines (oxPCs) in NSCLC patients.We identified eight lipid biomarkers that effectively differentiate between ADC and SCC subtypes using an untargeted approach. Notably, we observed a significant increase in plasma